Virulence of Metarhiziumisolates against the polyphagous defoliator pest, Spilarctia obliqua (Lepidoptera: Arctiidae) - Rajan, P. D. (2015)
Species of the entomopathogenic fungus Metarhizium are some of the most promising biocontrol agents against Lepidopteran pests. Laboratory bioassays were conducted to study the virulence of five isolates of Metarhizium sp. against larvae of the polyphagous pest, Spilarctia obliqua (Lepidoptera: Arctiidae). The Metarhizium isolates used in the study were recovered from soil and various insect hosts belonging to Lepidoptera, Coleoptera and Isoptera. Initially, a preliminary assay was carried out involving 18 Metarhizium isolates at a spore concentration 107 conidia ml-1 and five isolates, MIS 1, MIS 2, MIS 3, MIS 8 and MIS 9, which caused more than 50% mortality were chosen for the detailed bioassay. The assay was carried out with four different spore concentrations of each isolate, ranging from 104−107 conidia ml -1. The lethal concentration LC50 of these five isolates ranged from 2.1 × 105 to 38.9 × 105 conidia ml-1. The lethal time LT50 of the isolates ranged from 7.0−8.1, 6.0−7.7, 5.1−6.7, 4.6−5.4 days at concentrations 1 × 104, 1 × 105, 1 × 106, 1 × 107 conidia ml-1 respectively. The most pathogenic among the five isolates was the MIS 2 isolate with the lowest L50 of 2.11 × 105conidia ml-1 and LT50 of 4.6, 5.1, 6.0 and 7.0 days respectively at concentrations 1 × 107, 1 × 106, 1 × 105, 1 × 104conidia ml-1. Isolate MIS 3 was second in effectiveness. These two isolates showed promise for use as biocontrol agents against S. oblique.